2023
DOI: 10.3390/jfmk8020083
|View full text |Cite
|
Sign up to set email alerts
|

Reliability of a Smooth Pursuit Eye-Tracking System (EyeGuide Focus) in Healthy Adolescents and Adults

Abstract: Mild traumatic brain injury (mTBI) is the most common brain injury, seen in sports, fall, vehicle, or workplace injuries. Concussion is the most common type of mTBI. Assessment of impairments from concussion is evolving, with oculomotor testing suggested as a key component in a multimodality diagnostic protocol. The aim of this study was to evaluate the reliability of one eye-tracking system, the EyeGuide Focus. A group of 75 healthy adolescent and adult participants (adolescents: n = 28; female = 11, male = 1… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(7 citation statements)
references
References 40 publications
0
7
0
Order By: Relevance
“…To our knowledge, this is the first study to successfully implement pre-test familiarization using EyeGuide Focus (see Figure 2 ). These findings have shown that 2–4 practice trials are sufficient to offset familiarization effects seen in previous EyeGuide Focus research [ 24 ]. The group scores obtained in the current study (mean = 22,254.49 ± 5907.67 AUs) are lower than those reported in the original EyeGuide study (mean = 29,633.05 ± 9209.84 AUs) [ 21 ], higher than those reported in pro mixed-martial arts athletes (mean = 17,426.06 AUs) [ 28 ], but almost identical to scores recently reported in adults in their first trial (mean = 22,503.33 ± 7014.32) [ 24 ].…”
Section: Discussionmentioning
confidence: 60%
See 4 more Smart Citations
“…To our knowledge, this is the first study to successfully implement pre-test familiarization using EyeGuide Focus (see Figure 2 ). These findings have shown that 2–4 practice trials are sufficient to offset familiarization effects seen in previous EyeGuide Focus research [ 24 ]. The group scores obtained in the current study (mean = 22,254.49 ± 5907.67 AUs) are lower than those reported in the original EyeGuide study (mean = 29,633.05 ± 9209.84 AUs) [ 21 ], higher than those reported in pro mixed-martial arts athletes (mean = 17,426.06 AUs) [ 28 ], but almost identical to scores recently reported in adults in their first trial (mean = 22,503.33 ± 7014.32) [ 24 ].…”
Section: Discussionmentioning
confidence: 60%
“…There may be a number of reasons for the variations observed with this tool to date. Pearce et al recruited a population of physically active participants with no history of concussion, TBI, or visual conditions who were also not taking medication [ 24 ]. This differs from the present study and Fuller and Brown’s study, where previously concussed athletes and those with visual conditions were not excluded [ 25 ].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations